Dimethyl 3,3′-(phenylmethylene)bis(1H-indole-2-carboxylate) - Sun, Hong-Shun (International Union of Crystallography, 2013)
In the title compound, C(27)H(22)N(2)O(4), the two indole ring systems are approximately perpendicular to each other, with a dihedral angle of 84.5 (5)° between their planes; the benzene ring is twisted with respect to the two indole ring systems at angles of 78.5 (5) and 86.5 (3)°. In the crystal, molecules are linked by N—H⋯O hydrogen bonds, weak C—H⋯O and C—H⋯N hydrogen bonds, and C—H⋯π interactions into a three-dimensional supramolecular architecture.